Cripping criminology - Thorneycroft, Ryan (Theoretical criminology, 2021)
The position of disabled people within criminal justice frameworks and scholarship is one of ambivalence, which leaves disabled people in the simultaneous and contradictory position of centrality and marginality. While disabled people are over-represented within the criminal justice system (as offenders, victims, and witnesses), their voices are often marginalized or silenced. So too, while disabled people are over-represented within the criminal justice system, they remain under-explored in policy, practice, research, and scholarship. Aligning with the shift to queer and queering criminology, in this article we deploy the lens of ‘crip’ and ‘cripping’ to facilitate a more critical engagement with the concerns of disabled people, along with the mechanisms by which abledness informs criminal justice encounters.